Usefulness of rapid molecular tests in pediatric respiratory tract infections - Simona Nardi; Lorella Carolis; Roberta Iannini; Maria Vittoria De Sandro; Giovanna Solito; Matteo Calafatti; Camilla Gizzi (BMC, 2022)
Abstract Objective To evaluate the role and the advantages of nasopharyngeal swabs in the detection of Influenza A and B viruses and Respiratory syncytial virus through a rapid test based upon a nucleic acid amplification reaction in order to avoid improper antibiotics use. Design Case-control retrospective study. Setting Emergency Room of "Sandro Pertini" General Hospital, Rome, Italy. Participants Children (< 14 years old) who consecutively arrived in the Emergency Department (ED) for respiratory tract infections, without obvious signs of bacterial respiratory tract infections and other comorbidities, in the maximal seasonal incidence period of November-to-March of every year between 2016 and 2020. Methods Medical records of children included in the study were retrospectively examined. Children were subdivided according to the following intervals: 2016-2017 and 2017-2018 (Group 1), 2018-2019 and 2019-2020 (Group 2). Children in Group 2 undertook a nasopharyngeal swab, while those in Group 1 did not undergo any specific diagnostic test. Primary outcome Avoidance of improper antibiotics administration. Results A total of 386 children were included in the study: 174 in Group 1, 212 in Group 2. The Odd Ratio (OR) of prescribing an antibiotic in the groups of children not being swabbed compared to those of children undertaking a swab was 9.21 (CI95% 5.6-15.2, p < 0.001). The overall percentage of hospitalizations, both in the short observation unit or in the pediatric unit, did not differ between the two groups. Conclusions Nasopharyngeal swabs for the detection of Influenza A and B viruses and Respiratory syncytial virus proved to be a useful means to a correct and timely diagnosis and allowed for a significant reduction in the prescription of antibiotic therapy. Trial registration Retrospectively registered.